Development of an sRNA-mediated conditional knockdown system for Chlamydia trachomatis - Janina Ehses; Kevin Wang; Asha Densi; Cuper Ramirez; Ming Tan; Christine Sütterlin (mBio)
ABSTRACT We describe a new Chlamydia trachomatis protein depletion method that uses an engineered small RNA (sRNA) to inhibit translation of a target gene. In proof-of-principle experiments, we induced functional knockdown of IncA, a fusion-mediating inclusion membrane protein, as shown with Western blots, loss of IncA staining at the inclusion membrane, and production of multiple chlamydial inclusions within an infected cell. These effects were titratable and reversible. To test for polar effects, we separately targeted the inclusion membrane proteins IncE and IncG, which are expressed from the incDEFG operon. Knockdown of IncE caused loss of IncE and its interacting host protein SNX6 at the inclusion membrane, without affecting IncG protein levels. Similarly, IncG knockdown significantly reduced IncG levels and prevented recruitment of its interacting host protein 14-3-3β, without altering IncE protein levels. These data provide the first genetic evidence that IncE and IncG are necessary for the recruitment of SNX6 and 14-3-3β, respectively, demonstrating the value of this knockdown approach. We also successfully depleted the major chlamydial surface protein, major outer membrane protein (MOMP), which is encoded by a likely essential gene that has not been previously disrupted or knocked down. MOMP knockdown caused severe defects in bacterial morphology and progeny production. Thus, our sRNA-based approach has broad potential as a conditional knockdown method for studying the function of C. trachomatis genes, including essential genes and genes in an operon.IMPORTANCEWe describe a new method to reduce protein levels of a selected gene in the pathogenic bacterium Chlamydia trachomatis. This approach utilizes an engineered small RNA (sRNA) to inhibit translation of the mRNA for a target gene and produced inducible and reversible protein knockdown. Our method successfully knocked down four proteins, including a likely essential gene and individual genes in an operon, without altering protein levels of a neighboring gene. This conditional knockdown method will be useful for studying the function of genes in Chlamydia. It also has the potential to be applied to other obligate intracellular bacteria, including Rickettsia and Coxiella.